Vibration Analysis Of Gearmesh In Every Condition Using The Vibration Signal - Fadhila Ichsan, Fani Nur; , Wijianto, ST, M.Eng, Sc (2014)
The purpose of the research is to detect the defect of the gear on the gearbox using vibration signal analysis. The experiment was done on four condition of gear. Gears are in good condition, a half broken tooth, one broken tooth, and cracked. The gear rotational speeds were taken in 300 rpm, 750 rpm, and 2250 rpm. Vibration data acquisition was done using vibrationmeter and PC. Vibrationmeter record the signal on time domain and convert it to frequency domain. Defect analysis was done in the time domain and frequency domain. Experiment result showed that time domain, defect of gear could detected by spike appearing every one period of shaft revolution. This case was indication of gear having broken one broken tooth. Then, on two broken teeth, amplitude of spike period was smaller than one broken tooth condition. Whereas on a half broken tooth condition failure was difficult to detect at time domain. At frequency domain, indication of a half broken tooth was seen by increasing amplitude of gearmesh frequency four time to 39,57 volt and sideband appearing. Then on one broken tooth indication could be seen by increasing amplitude of gearmesh frequency ten times to 123,5 volt and sideband appearing. On cracked gear, indication could be seen by increasing amplitude of gearmesh frequency four times to 123,5 volt and appearing many sidebands. Every sideband have a distance a shaft revolution frequency. Sideband appearing and increasing amplitude of gearmesh can be detected as failure of gearbox.